2015
DOI: 10.1128/aac.00369-15
|View full text |Cite
|
Sign up to set email alerts
|

The New Macrolide-Lincosamide-Streptogramin B Resistance Gene erm (45) Is Located within a Genomic Island in Staphylococcus fleurettii

Abstract: Genome alignment of a macrolide, lincosamide, and streptogramin B (MLS B )-resistant Staphylococcus fleurettii strain with an MLS B -susceptible S. fleurettii strain revealed a novel 11,513-bp genomic island carrying the new erythromycin resistance methylase gene erm(45). This gene was shown to confer inducible MLS B resistance when cloned into Staphylococcus aureus. The erm(45)-containing island was integrated into the housekeeping gene guaA in S. fleurettii and was able to form a circular intermediate but wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…All Tn5801 platforms identified in enterococci in this study were chromosomally located at the 3= end of guaA, as previously observed for three emblematic Tn5801 elements of staphylococci, Clostridium, and S. agalactiae (13,28). In the available sequences of the Tn5801 variants was the 11-bp sequence described previously as direct repeats (DRs) situated within the 3= end of guaA (13). All guaA sequences within the same species had high similarity (99 to 100%), which was somewhat lower (70 to 80%) when comparing isolates from different species.…”
Section: Screening Of Tn5801 In Genbank Databases and Creation Of Datsupporting
confidence: 56%
See 1 more Smart Citation
“…All Tn5801 platforms identified in enterococci in this study were chromosomally located at the 3= end of guaA, as previously observed for three emblematic Tn5801 elements of staphylococci, Clostridium, and S. agalactiae (13,28). In the available sequences of the Tn5801 variants was the 11-bp sequence described previously as direct repeats (DRs) situated within the 3= end of guaA (13). All guaA sequences within the same species had high similarity (99 to 100%), which was somewhat lower (70 to 80%) when comparing isolates from different species.…”
Section: Screening Of Tn5801 In Genbank Databases and Creation Of Datsupporting
confidence: 56%
“…Tn5801 has a site-specific tyrosine recombinase that recognizes the 3= end of the GMP synthase gene (guaA) (10,11), an insertion hot spot of genomic islands coding for pathogenicity or antibiotic resistance in different Firmicutes (12)(13)(14). Tn5801 was originally detected in the vancomycin-resistant Staphylococcus aureus (VRSA) clinical strain Mu50 recovered in Japan in 1997 (15), but several studies have documented the presence of platforms highly similar to Tn5801 in early isolates of Streptococcus agalactiae (France, 1953) (1), S. aureus (Denmark, 1963; designated Tn6014) (3), and Clostridium perfringens (United States, 1977; a truncated element designated CW459tet(M)] (16).…”
mentioning
confidence: 99%
“…Further investigation into gp69 with HHblits revealed high sequence identity to Erm(45) of Staphylococcus fleurettii (HHblits: 100% probability, 2.4e-104 E -value). Researchers identified Erm(45) as the enzyme responsible for increased erythromycin resistance in some strains of S. fleuretti ( Wipf et al, 2015 ). The erm gene ( e rythromycin r ibosome m ethylase) encodes a methylase enzyme that provides macrolide resistance by methylating the erythromycin target-site on the ribosome ( Prunier et al, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Along with the erm(44) and erm(45) genes, which were also recently identified in staphylococci from bovine mastitis milk (9,22,23), the discovery of erm(48) highlights the role of dairy cows as a source of new MLS B resistance genes. Accession number(s).…”
Section: Figmentioning
confidence: 99%